Unfolding the Connection between the Kantian Self and Time - Volkan Çifteci (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
In Kant’s Critique of Pure Reason, the self and time are interwoven on three different levels. To unveil this relation, this paper refers back to Kant’s criticism directed to the ideas of early modern philosophers concerning the two notions in question. On the three levels, three different conceptions of the self correspond to three aspects of time. In the first aspect we encounter the self as inner sense (appearance) and time reveals itself as the form of this sense. The first aspect of the self thus cannot be known as it is in itself; on the contrary, it can be known only as an appearance. Later, in virtue of the act of imagination, while the second aspect of the self is unfolded as a temporal self, time comes forth as formal intuition. In this level, the self starts to become conscious of its temporal character. Finally, in the third aspect, the relation between the transcendental unity of the self (apperception) and the unity of time becomes transparent. In the course of analyzing the three corresponding aspects of the self and time, this paper aims to reveal both the temporal character of the Kantian self and the subjective character of time.